2001
DOI: 10.1007/s004640090122
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic left colon resection for diverticular disease

Abstract: The feasibility of the laparoscopic approach to diverticular disease is established with a conversion rate of 4%, a low incidence of acute septic complications (5.3%), and a mortality rate of 0%. Therefore, laparoscopic sigmoid colectomy has become our procedure of choice in the treatment of diverticular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
2
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 17 publications
10
29
2
4
Order By: Relevance
“…Stricture of the anastomosis occurred in 3.41% of our patients, which is comparable to most studies (0.5-5.9%) and can be explained by the inflammatory process 4,17 ,and the stapler size, specially if diameters less than 28 mm are used 5 . Even though sexual dysfunction is a feared complication after such operation, our series included 98 men and only one of them had to deal with this issue which was a transient problem managed conservatively.…”
Section: Discussionsupporting
confidence: 87%
“…Stricture of the anastomosis occurred in 3.41% of our patients, which is comparable to most studies (0.5-5.9%) and can be explained by the inflammatory process 4,17 ,and the stapler size, specially if diameters less than 28 mm are used 5 . Even though sexual dysfunction is a feared complication after such operation, our series included 98 men and only one of them had to deal with this issue which was a transient problem managed conservatively.…”
Section: Discussionsupporting
confidence: 87%
“…3 Overall, recent studies of laparoscopic management of complicated diverticulitis have demonstrated that in capable hands, operating times and conversion rates are acceptable, and morbidity and mortality rates are comparable with open surgery. 2,6,7,43,[55][56][57][58] …”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
“…Compared with open surgery, laparoscopic surgery offers many benefits, such as smaller surgical wounds, good esthetic results, less pain, decreased use of analgesics, early recovery of intestinal peristalsis, and a shorter hospital stay [10][11][12][13][14][15][16][17][18][19] . In terms of inflammatory cytokine levels, however, the minimal invasiveness of laparoscopic surgery remains controversial.…”
Section: Colon Cancermentioning
confidence: 99%